Peningkatan Kinerja Pengurus Koperasi Ramot Berjaya Melalui Manajemen SDM - Togar Naibaho; Syah Paradiba Sari Sirait; Jenny Ester Pandiangan; Winfrontstein Naibaho (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Cooperatives play a strategic role as one of the pillars of the community economy in improving the welfare of their members. However, the performance of cooperative management is often not optimal due to limitations in human resource (HR) management. This Community Service activity aims to improve the performance of the management of Koperasi Ramot Berjaya through the implementation of effective human resource management practices. The methods used include socialization, training, and mentoring related to HR planning, task division, competency development, and performance evaluation. The activities were carried out in a participatory manner involving all cooperative management members. The results show an increase in the management’s understanding of HR management concepts, improvements in work systems, and enhanced effectiveness and productivity in carrying out their duties. In addition, the management has begun to implement clearer job descriptions and conduct regular performance evaluations. Therefore, the application of proper HR management has proven to be effective in sustainably improving the performance of cooperative management. This activity is expected to serve as a model for other cooperatives in optimizing HR management to enhance organizational competitiveness.